EFFECT OF FOLIAR APPLICATION OF GA3, ETHREL AND COPPER SULPHATE ON FLOWERING BEHAVIOUR AND YIELD OF JATROPHA CURCAS L. - GAYAKVAD, PARESH; D. B. JADEJA; M. B. TANDEL; M. R. PARMAR; BHALAWE , SHAILENDRA; D. NAYAK (The Bioscan, 2014)
Effect of various plant growth substances viz., GA3 (25, 50,100ppm), Ethrel (1500, 2000, 2500ppm), Copper sulphate (0.1, 0.2, 0.5%) as foliar spray treatment applied during January to October was studied at 15 days intervals. The flowering behaviour, sex-expression and yield of Jatropha curcas L was investigated during in Randomized Block Design (RBD) at the College Farm, Navsari. Looking to the results, it was noticed that GA3 50ppm resulted in increased number of inflorescence per plant(31.25), number of flower per inflorescence (76.87), number of (male 94.75/female 4.01) flowers, flower sex ratio (24.22), number of fruits per inflorescence (3.71), number of fruits per plant (88.0) and fruit(453.33) as well as seed (355.55) yield per plants in plant treated with GA3 50ppm as compared to control between 9th to 14th spray. The Male: Female flower ratio was the lowest at 14th spray stage under majority of treatments indicating increased number of female flowers which is ultimately reflected by increased fruit and seed yield. Ethrel 2000 ppm and GA3100ppm followed GA3 50ppm in its similar effects.